2017
DOI: 10.4049/jimmunol.1601165
|View full text |Cite
|
Sign up to set email alerts
|

Talin Plays a Critical Role in the Maintenance of the Regulatory T Cell Pool

Abstract: Talin, a cytoskeletal protein essential in mediating integrin activation, has been previously shown to be involved in the regulation of T cell proliferation and function. Here we describe a role for talin in maintaining the homeostasis and survival of the regulatory T (Treg) cell pool. T cell-specific deletion of talin in Tln1fl/flCd4Cre mice resulted in spontaneous lymphocyte activation, primarily due to numerical and functional deficiencies of Treg cells in the periphery. Peripheral talin-deficient Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
(72 reference statements)
3
28
0
Order By: Relevance
“…The resulting changes in lymphocyte–APC interaction are likely to have far-reaching effects. For example, loss of talin has recently been found to perturb regulatory T cell homeostasis ( 69 ). With respect to costimulatory signaling, molecules such as Rap1, FAK, and Pyk2 that regulate the function of clutch proteins may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting changes in lymphocyte–APC interaction are likely to have far-reaching effects. For example, loss of talin has recently been found to perturb regulatory T cell homeostasis ( 69 ). With respect to costimulatory signaling, molecules such as Rap1, FAK, and Pyk2 that regulate the function of clutch proteins may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…LFA-1 crosstalk with Notch signaling has been shown to induce IFNγ production and re-enforce Th1 cell functions suggesting that LFA-1 engagement with tissue resident APCs will further strengthen T cell differentiation ( 103 ). Similarly, Tregs have been shown to require talin and LFA-1 activation to induce IL-2Rα upregulation, which is required for Treg function ( 104 , 105 ). Additionally, we recently demonstrated that an intracellular pool of LFA-1 is relocalized to the cell surface upon initial T/APC interactions and plays a key role in T cell memory development ( 76 ).…”
Section: Lfa-1 and T Cell Activationmentioning
confidence: 99%
“…33 TLN1 encodes a cytoskeletal protein, talin-1, that has been implicated in phagocytosis, as well as regulates T cell proliferation and functions. 34, 35…”
Section: Resultsmentioning
confidence: 99%